2022
DOI: 10.3389/fimmu.2022.830482
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Antibody, B Cell and Fc Receptor Interactions to Understand Heterogeneous Immune Responses in Tuberculosis

Abstract: Despite over a century of research, Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), continues to kill 1.5 million people annually. Though less than 10% of infected individuals develop active disease, the specific host immune responses that lead to Mtb transmission and death, as well as those that are protective, are not yet fully defined. Recent immune correlative studies demonstrate that the spectrum of infection and disease is more heterogenous than has been classically defined. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 285 publications
(371 reference statements)
0
10
0
Order By: Relevance
“…Using a mouse model, we examined the vaccine’s immunogenicity ( Figure 2A ). Protective antibodies may promote and increase the death of intracellular bacteria through FcR-mediated phagocytosis and improve immune responses through the rapid adsorption and processing of antigens ( 29 ). Therefore, we purified the fusion protein for the evaluation of serum antibody levels in mice after immunization ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using a mouse model, we examined the vaccine’s immunogenicity ( Figure 2A ). Protective antibodies may promote and increase the death of intracellular bacteria through FcR-mediated phagocytosis and improve immune responses through the rapid adsorption and processing of antigens ( 29 ). Therefore, we purified the fusion protein for the evaluation of serum antibody levels in mice after immunization ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings suggest impaired serum humoral responses against Mtb occur relatively early (< 6 months) following SIV infection. The SIV‐coinfected animals studied here had lower total CD4 + T‐cell counts at the time of Mtb coinfection, 16 and it is possible that the reduced T‐cell repertoire may impair the antibody response given the important roles of CD4 + T cells in providing B‐cell help 31 …”
Section: Discussionmentioning
confidence: 96%
“…The SIV-coinfected animals studied here had lower total CD4 + T-cell counts at the time of Mtb coinfection, 16 and it is possible that the reduced T-cell repertoire may impair the antibody response given the important roles of CD4 + T cells in providing B-cell help. 31 Our work was performed with a small cohort of 15 macaques (seven SIV-positive, eight SIV-na€ ıve), which may limit the strength of our conclusions. Whether these observations apply to human cohorts remains to be confirmed.…”
Section: Discussionmentioning
confidence: 98%
“…26 Our KEGG analysis data showed that NF-κB, B cell receptor, Fc epsilon RI, and Toll-like receptor signaling pathways were enriched in the TB group compared with NonTB or ParaTB groups. Thereinto, the NF-κB signaling pathway is up-regulated considerably in active TB patients and regulates immune response, 9 B cells modulate IL-10 and inflammation during Mtb infection, 27 Fc receptors on immune cells can influence TB's local and systemic adaptive immune responses, 28 and Toll-like receptors are the essential pattern recognition receptors detecting Mtb in the first step of initiation. 25 These signaling pathways are substantially involved in the early immune reaction of encountering Mtb.…”
Section: ■ Discussionmentioning
confidence: 99%